Methodological quality of systematic reviews and clinical trials on women's health published in a Brazilian evidence-based health journal (Clinics, 2013)
OBJECTIVES: To assess the quality of systematic reviews and clinical trials on women's health recently published in a Brazilian evidence-based health journal. METHOD: All systematic reviews and clinical trials on women's health published in the last five years in the Brazilian Journal of Evidence-based Health were retrieved. Two independent reviewers critically assessed the methodological quality of reviews and trials using AMSTAR and the Cochrane Risk of Bias Table, respectively. RESULTS: Systematic reviews and clinical trials accounted for less than 10% of the 61 original studies on women's health published in the São Paulo Medical Journal over the last five years. All five reviews were considered to be of moderate quality; the worst domains were publication bias and the appropriate use of study quality in formulating conclusions. All three clinical trials were judged to have a high risk of bias. The participant blinding, personnel and outcome assessors and allocation concealment domains had the worst scores. CONCLUSIONS: Most of the systematic reviews and clinical trials on women's health recently published in a Brazilian evidence-based journal are of low to moderate quality. The quality of these types of studies needs improvement.